Nilai-Nilai Pendidikan Karakter dalam Buku Ajar Al-Qur’an Hadis pada Madrasah Aliyah - Ulfah Rahmawati; Fariq Fahrun Nisa; Niswatun Azizah; Bahrudin * (LP2M IAIN kUDUS, 2022)
The textbook used in the Al-Qur'an Hadith subject in Class XI at Madrasah Aliyah is a textbook that is used as a reference during the learning process in class by educators and students, which contains competencies about character-based education or good manners integrated into the subject textbooks by including them in the core competencies and basic competencies number one and two, namely regarding the integration of religious attitudes and social attitudes. In obtaining data in this study using qualitative methods and data collection is done by means of content analysis on the content of the material in the book. This research aims to describe and elaborate on the values in education about manners contained in the textbooks used in the Al-Qur'an Hadith class XI subject at the Madrasah Aliyah level in even semesters. The results of this research and study in chapter VIII on the work ethic of a Muslim person, chapter IX on halal and good food and chapter X on gratitude to Allah SWT, show the value of character education contained in the three chapters which includes religious values, nationalist values, independence values, integrity values, and mutual cooperation values.